1985
DOI: 10.1207/s15327752jpa4902_14
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Local versus Standard MMPI Norms: A Comment

Abstract: This note shows that evidence considered by Wooten (1984) to support claims of diagnostic superiority of standard over local MMPI norms, may mainly reflect the fact that a large proportion of the group tested by Wooten's consisted of persons with emotional, behavioral problems. Reevaluation of Wooten's data suggests a range of conditions under which Wooten's diagnostic criterion used with local norms is superior to the same criterion used with standard norms, and another range of conditions under which this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Such practices would be extremely problematic from a liability perspective. It is also worth noting that Hsu (1985) found that local cut scores are not necessarily superior to global cut scores, but the truth is that resistance to local cut scores is more practical than it is statistical. Note.…”
Section: Bayes's Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Such practices would be extremely problematic from a liability perspective. It is also worth noting that Hsu (1985) found that local cut scores are not necessarily superior to global cut scores, but the truth is that resistance to local cut scores is more practical than it is statistical. Note.…”
Section: Bayes's Theoremmentioning
confidence: 99%
“…2Following Meehl and Rosen (1955), expository writing on diagnostic efficiency for psychologists often notes that in cases where the BR is extremely low or high, use of the test may result in a lower CF than does “betting the base rate” (i.e., always predicting that the respondent is a member of the modal population; Hsu, 1985; Waller, Yonce, Grove, Faust, & Lezenweger, 2006). Although this is technically true, betting the BR is unacceptable in applied settings for very practical reasons.…”
mentioning
confidence: 99%